TGFU SEBUAH INOVASI PEMBELAJARAN PERMAINAN - Sri Winarni Winarni (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2008)
Teaching Games for Understanding (TGfU) as a taching model now is getting well-known internationally. As a new emerging idea, TGfU evolves in agreement and disagreement. An inovation needs supporters and inovation agents. In specific purpose to introduce TGfU for teachers and prospectus PE teachers, the efforts need to be done in step by step on the agencies such as teachers, principals, students teachers, researchers, experts, and programs at teacher education institutions. In addition, it is also important to consider the aspects influencing the acceleration of that inovation along with its attributes. Kata kunci: Inovasi, Pembelajaran penj